2014
DOI: 10.1371/journal.pone.0109790
|View full text |Cite|
|
Sign up to set email alerts
|

Oral Manifestations in the American Tegumentary Leishmaniasis

Abstract: IntroductionAmerican tegumentary leishmaniasis (ATL) can affect the skin or mucosa (mucocutaneous leishmaniasis – MCL) including the oral cavity. MCL oral lesions are often confused with other oral diseases, delaying diagnosis and specific treatment, and increasing the likelihood of sequelae. Thus, increasing the knowledge of the evolution of ATL oral lesions can facilitate its early diagnosis improving the prognosis of healing.ObjectivesEvaluate the frequency of ATL oral lesion and describe its clinical, labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
2
10
0
6
Order By: Relevance
“…Despite that, only 0.25% of the patients initially treated for CL developed ML. At NIID, all ATL patients, regardless of mucous membranes complaint, are systematically evaluated by endoscopic methods that allow early diagnosis and treatment of mucosal lesions, including patients erroneously referred to initially as CL cases ( Costa et al 2014 ). This may explain why the concomitant form (simultaneous presence of cutaneous and mucosal lesions) is the most common form of ML at NIID and consequently, in Rio de Janeiro State.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, only 0.25% of the patients initially treated for CL developed ML. At NIID, all ATL patients, regardless of mucous membranes complaint, are systematically evaluated by endoscopic methods that allow early diagnosis and treatment of mucosal lesions, including patients erroneously referred to initially as CL cases ( Costa et al 2014 ). This may explain why the concomitant form (simultaneous presence of cutaneous and mucosal lesions) is the most common form of ML at NIID and consequently, in Rio de Janeiro State.…”
Section: Discussionmentioning
confidence: 99%
“…Probably this symptom is undervalued by sick people who take longer to seek for medical attention. On the other hand, we observed that symptoms such as odynophagia occur with greater discomfort, decreased food intake and consequent weight loss which can reduce the time for seeking for medical help [ 26 , 27 ]. In the same manner, the lack of specific symptoms [ 3 ] and the insidious nature of LTB, together with the difficult access of patients to medical attention and specialized exams [ 14 ], may delay diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, similarly to Wang et al (2007), we found no evidence that the delay in the diagnosis predisposes the patient to larger laryngeal lesions [ 16 ]. It is possible that the extent of the laryngeal lesion is not necessarily part of the natural history of the disease, but a more serious outcome in some patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This form is usually secondary to the cutaneous one when it is not correctly treated or is lef untreated, but, in rare cases, it can be primary 2 . In comparison with other mucosal sites, the mouth has a shorter evolution time 3 .…”
Section: Introductionmentioning
confidence: 99%